2022
DOI: 10.1021/acs.est.2c00226
|View full text |Cite
|
Sign up to set email alerts
|

Co-exposure of Monensin Increased the Risks of Atrazine to Earthworms

Abstract: Antibiotics could enter farmlands through sewage irrigation or manure application, causing combined pollution with pesticides. Antibiotics may affect the environmental fate of pesticides and even increase their bioavailability. In this study, the influence of monensin on the degradation, toxicity, and availability of atrazine in soil-earthworm microcosms was investigated. Monensin inhibited the degradation of atrazine, changed the metabolite patterns in soil, and increased the bioavailability of atrazine in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Similar to our study, reduced cocoon production and downregulation of Ann genes in earthworms have been widely reported after pollutant exposure. ,, Interestingly, Lin et al found that an artificial sweetener, acesulfame (10 mg/kg), induced an increase in cocoon production in E. fetida.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our study, reduced cocoon production and downregulation of Ann genes in earthworms have been widely reported after pollutant exposure. ,, Interestingly, Lin et al found that an artificial sweetener, acesulfame (10 mg/kg), induced an increase in cocoon production in E. fetida.…”
Section: Resultssupporting
confidence: 91%
“…These preliminary indications suggest that S-(+)-MFZ is more reproductively toxic than R-(−)-MFZ. Furthermore, key genes Ann associated with earthworm reproduction were characterized . Rac, R-(−), and S-(+) groups downregulated expression by 33.3, 57.0, and 71.7%, respectively, compared with the control group (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid molecules play indispensable roles in cells, especially, serving as the “building blocks” of the cell membrane to establish the critical barrier between the cell and outer environment for maintaining normal cellular function. , The growing reports indicated that exposure to environmental pollutants would perturb lipid homeostasis, which was the vital factor for impairing the cytoarchitecture and causing cellular dysfunction. For example, previous publications revealed that the lipid peroxidation in cells exposed to exogenous substances such as nanomaterials induced the disruption of the cytomembrane and the loss of cell viability . Also, Shanta et al have linked the lipid fluctuations in microalga cells (Chlamydomonas reinhardtii) triggered by herbicides with the cytotoxic effects of herbicides on C.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with previous studies, ATZ is toxic to several organisms, with ecotoxicity studies involving hydrobios, earthworms, algae, and others. 31,32 Pesticides ingested into organisms are metabolized by the liver, which is the main metabolic organ, and lead to various hepatic disorders. Apoptosis and alterations in metabolite composition of liver cells of mice induced by ATZ have been reported.…”
Section: Discussionmentioning
confidence: 99%